Tal Como Somos/Just As We Are: An Educational Film to Reduce Stigma towards Gay and Bisexual Men, Transgender Individuals & Persons Living with HIV/AIDS - Ramirez-Valles, Jesus (2013)
In this paper we describe the development and dissemination of a film-based educational intervention to reduce negative attitudes towards gay and bisexual men and transgender women (GBT) and people living with HIV/AIDS (PLWHA) in Latino communities, with a focus on youth. The intervention, Tal Como Somos/Just as We Are, is based on stigma and attribution theories, extensive formative research, and community input. Evaluation findings among educators and school youth suggest the film has the potential to effectively impact attitudes towards GBT and PLWHA. The film and intervention are being disseminated using diffusion of innovations theory through community-based organizations, schools, television broadcasting and film festivals.